Legal Protection for Fixed-Term Workers in the Drafting of an Employment Agreement - Zen Mutowali; Horadin Saragih; Zulfikar Judge; Joko Widarto (GoAcademica Research & Publishing, 2026)
Fixed-Term Employment Agreements (Perjanjian Kerja Waktu Tertentu/PKWT) are widely used by companies to flexibly meet labor needs. However, in practice, PKWTs are often drafted with clauses that disadvantage workers, resulting in contractual injustice. This study aims to analyze the forms of government protection for workers under PKWT arrangements and the drafting of fair PKWT clauses. This research employs normative legal research with statutory and conceptual approaches, supported by legal protection theory, contract theory, and justice theory. The findings indicate that government protection is implemented through labor regulations, supervision, and industrial dispute resolution mechanisms. Nevertheless, such protection remains largely passive, as labor offices merely record PKWTs without reviewing the substance of their clauses. Meanwhile, fair PKWT drafting should reflect the principles of balance and good faith, which are often absent in practice. This study concludes that although legal instruments governing PKWT are comprehensive, there remains a significant gap between regulation and implementation. Strengthening supervision and law enforcement is therefore necessary to ensure contractual justice for workers.